OPTIMALISASI WAKTU DAN BIAYA PELAKSANAAN PROYEK MENGGUNAKAN METODE LEAST COST ANALYSIS (Studi Kasus : Pembangunan Pasar Amlapura Barat) - Dewi, Anak Agung Diah Parami; Yana, Anak Agung Gede Agung; Dwinanjaya, Kadek Yasasi (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 24, No. 2, Juli 2020DO - 10.24843/JITS.2020.v24.i02.p10, 2021)
Abstract: Construction projects can be completed successfully based on careful planning. However, in the implementation of the West Amlapura Market development project, it requires an additional 50 calendar days to complete the work where the project is delayed by 24.468% in the 20th week with the remaining approximately one month deadline for working days, due to some constraints at the initial stage or determination zero point building level, mobility of tools and materials that hinder and limited Human Resources. Delays in work on the West Amlapura Market development project can be anticipated by accelerating the implementation of the project, with the hope that costs will be minimal while still paying attention to the established quality standards. This study aims to analyze the optimum time and cost by adding labor. This study uses the Least Cost Analysis method which aims to obtain the optimal project duration with the minimum total project cost calculated from activities that have the lowest cost slope. The data required in this study are secondary data in the form of a Budget Plan (RAB), Time Schedule and a List of Unit Price Analysis obtained from the contractor. Based on the calculation of the least cost analysis with the addition of optimum compression labor, it is found that the reduction in the duration of completion is 52 days from a late time of 133 days to 81 days with a total cost of Rp. 11,759,553,889, direct costs of Rp. 11,481,213,347 and indirect costs of Rp. Rp. 278,340,542, -